Hematological and Molecular Characterization of a Novel Hb A2 Variant with Homozygous α-Thalassemia-2 in a Southern Thai Individual. (4th May 2017) - Nuinoon, Manit; Jeenduang, Nutjaree; Kesornsit, Aumpika; Horpet, Dararat; Plyduang, Thunyaluk
Abstract: We report here the hematological and molecular features of a novel δ-globin chain variant found in a Southern Thai woman. Her complete blood count was as follows: red blood cell (RBC) count 5.90 × 10 12 /L, hemoglobin concentration (Hb) 12.6 g/dL, packed cell volume (PCV) 0.41 L/L, mean corpuscular volume (MCV) 69.5 fL, mean corpuscular Hb (MCH) 21.4 pg, mean corpuscular Hb concentration (MCHC) 30.7 g/dL and RBC distribution width (RDW) 13.1%. The blood smear demonstrated microcytic hypochromic RBCs suggestive of thalassemia trait. Hemoglobin analysis identified Hb A2 + Hb A2 -Kiriwong (2.4%) and Hb F (0.1%) on high performance liquid chromatography (HPLC). To characterize the α-thalassemia (α-thal) genotype, common α-thal-1 and α-thal-2 alleles were characterized by multiplex gap-polymerase chain reaction (gap-PCR). The results revealed homozygous α-thal-2 (–α 3.7 /–α 3.7 ) in this case. DNA sequencing showed the presence of a novel δ-globin gene mutation [δ77(EF1)His→Arg; HBD : c.233A>G] that we named Hb A2 -Kiriwong for the village from where the proband lived. In summary, the presence of microcytic hypochromic RBCs in this case was likely the result of the homozygous –α 3.7 (rightward) deletion and was not affected by this Hb A2 variant.